Dialogic communication management theory and engagement with investors - Muriel Serfontein-Jordaan; Dawie Bornman (Communicare)
Considering the recent corporate scandals faced by the South African capital market, stakeholders are understandably more sceptical about the accuracy and transparency of information being communicated to them. An integral stakeholder group which forms part of the success of an organisation is its investors. Since investors have increasing demands and specific information needs, it is essential that organisations communicate relevant and useful information by means of investor relations. However, despite its importance, academic research in the field of investor relations, specifically in terms of communication, is lacking and does not correlate with the importance of the function in corporate practice. The aim of this study was to critically evaluate the current IR practices of JSE listed organisations; to determine whether these aforementioned organisations participate in dialogic engagement with investors. This was done by investigating investor relations theory within the broader context of dialogic theory. The research design employed in this study was an interpretive multiple case study qualitative inquiry. The findings are the culmination and outcome of a synthesis of an in-depth literature review, a content analysis of communicative products- and semi-structured interviews with the investor relations officers of the case organisations.